Analysis of Character Education in the Storybook of The Champion Who Has a Soft Heart by Yusman Nasution (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
The current era can be witnessed by phenomena shows the decharacterization of the nation. The formation of character of learning is the full responsibility of the teacher then can insert character education through learning that will be delivered to students. The aims of this research are (1) to describe the structure (2) To describe the values of character education in the books (3) Explaining the relevance of learning literature in elementary school. This research uses a qualitative descriptive. Techniques using interviews and document analysis. Data sources include a children's fiction book entitled